2013
DOI: 10.1111/tpj.12355
|View full text |Cite
|
Sign up to set email alerts
|

Next‐generation sequencing, FISH mapping and synteny‐based modeling reveal mechanisms of decreasing dysploidy in Cucumis

Abstract: SUMMARYIn the large Cucurbitaceae genus Cucumis, cucumber (C. sativus) is the only species with 2n = 2x = 14 chromosomes. The majority of the remaining species, including melon (C. melo) and the sister species of cucumber, C. hystrix, have 2n = 2x = 24 chromosomes, implying a reduction from n = 12 to n = 7. To understand the underlying mechanisms, we investigated chromosome synteny among cucumber, C. hystrix and melon using integrated and complementary approaches. We identified 14 inversions and a C. hystrix l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 64 publications
2
88
1
Order By: Relevance
“…Cucumber chromosome 7 (C7) has maintained a complete synteny with a single chromosome in the Cucumis species without interchromosomal rearrangements (Huang et al 2009;Yang et al 2014). Comparative genetic and genomic studies revealed a high degree of synteny and collinearity in the long arm of C7 (8 Mb) across the Cucumis species and beyond (Yang et al 2014). Thus, C7 provides an ideal target to test crossspecies chromosome painting using bulked oligo probes.…”
Section: Cross-species Chromosome Painting Using Bulked Oligosmentioning
confidence: 99%
See 1 more Smart Citation
“…Cucumber chromosome 7 (C7) has maintained a complete synteny with a single chromosome in the Cucumis species without interchromosomal rearrangements (Huang et al 2009;Yang et al 2014). Comparative genetic and genomic studies revealed a high degree of synteny and collinearity in the long arm of C7 (8 Mb) across the Cucumis species and beyond (Yang et al 2014). Thus, C7 provides an ideal target to test crossspecies chromosome painting using bulked oligo probes.…”
Section: Cross-species Chromosome Painting Using Bulked Oligosmentioning
confidence: 99%
“…Seeds of all PI lines were obtained from the U.S. National Plant Germplasm System (Ames, IA). An interspecific F 1 hybrid between C. hystrix (accession TH1) and cucumber inbred line Gy14 was developed with embryo rescue (Yang et al 2014) and used for homeologous chromosome pairing study.…”
Section: Plant Materialsmentioning
confidence: 99%
“…In Cucumis sativus, a similar mix of mechanisms led to dysploid chromosome reduction from an n = 12 ancestor to the n = 7 karyotype of cucumber (Yang et al 2013). Different from the other genera so far studied, large and small chromosome pairs are identifiable in the karyotype the two Jarilla species ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1), possibly involving reduction a fusion of two chromosomes, which would explain the change from n = 9 to n = 8. Dysploid reductions in chromosome number have been analyzed in detail in Arabidopsis (Yogeeswaran et al 2005;Mandakova and Lysak 2008), Triticeae (Luo et al 2009), and recently Cucumis in fully sequenced genomes of cucumber and its sister species were compared (Yang et al 2013). In…”
Section: Resultsmentioning
confidence: 99%
“…This variability plays a critical role in species evolution and has been considered to be a consequence of chromosome rearrangement (Faria and Navarro 2010;Heslop-Harrison and Schwarzacher 2011). Such rearrangement may increase or decrease the chromosome number in the karyotype and is termed ascending or descending dysploidy (Schubert and Lysak 2011;Leitch et al 2013;De Storme and Mason 2014;Yang et al 2014).…”
Section: Introductionmentioning
confidence: 99%